2018
DOI: 10.1016/j.ijcha.2018.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Age modifies the risk of atrial fibrillation among athletes: A systematic literature review and meta-analysis

Abstract: BackgroundThe relationship between competitive sports and atrial fibrillation (AF) is controversial. We aimed to systematically evaluate and summarize all published observational data on the association between competitive sports and AF.Methods and resultsWe searched PubMed, EMBASE, Scopus and SportDiskus for all observational studies that assessed the risk of AF among athletes involved in competitive sports. Data were extracted and pooled odds ratios (OR) were calculated using random effects models. Six cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…On the contrary, the findings provided by a recent meta-analysis including six cohort studies and two case-control studies with a total of 9113 subjects showed a significantly increased risk of incident and prevalent AF among athletes compared to the general population (OR = 1.64; CI: 1.10-2.43). 37 In addition to LA dilatation, several other mechanisms, alone or in combination, could contribute to atrial fibrillation in competitive athletes. Vagal tone and bradycardia are more prevalent in athletes, and bradycardia has been associated with atrial fibrillation in individuals with normal cardiac structure and function.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, the findings provided by a recent meta-analysis including six cohort studies and two case-control studies with a total of 9113 subjects showed a significantly increased risk of incident and prevalent AF among athletes compared to the general population (OR = 1.64; CI: 1.10-2.43). 37 In addition to LA dilatation, several other mechanisms, alone or in combination, could contribute to atrial fibrillation in competitive athletes. Vagal tone and bradycardia are more prevalent in athletes, and bradycardia has been associated with atrial fibrillation in individuals with normal cardiac structure and function.…”
Section: Discussionmentioning
confidence: 99%
“…The third meta-analysis published in 2018 identified six cohort studies and two case-control studies totaling 9113 individuals. Athletes were at increased risk of AF (odds ratio 1.64); however, when adjusted for age, this effect was only identified in those < 54 years of age [ 29 ]. Older athletes were not at increased risk of AF compared to age-matched sedentary controls.…”
Section: Methodsmentioning
confidence: 99%
“…20 Furthermore, several meta-analysis showed that the risk of AF is significantly higher in athletes compared with non-athletes. 25,26 Baseline obesity and weight gain are well-established independent risk factors for AF. 13,[27][28][29] Several studies have demonstrated that the association between obesity and AF risk can be modified by physical activity, suggesting that by improving fitness the adverse effect of obesity can be attenuated.…”
Section: Discussionmentioning
confidence: 99%